Digital fabrication and revival craft in Latin America: Alliance between designers and artisans - Herrera Polo, Pablo C. (2016)
Latin America has experienced scripting and digital fabrication, and the alliance between designers and artisans. Taking into account that the revival of crafts has proved very promising in Latin America (Borges, 2015), the objective of this research is to analyse the diversity of cases and select those where designers took an interest for strengthening the artisans’ jobs in the field of pottery and textiles. We found that both revitalised the identity and cultural tradition in their own countries, in a moment when craft seemed to drop in front of industrial production. By preserving traditional materials, pieces continue to be unique and customizable, transcending thus their local origin towards new global markets.